BEHAVIOR IN ADOLESCENTS - PSYCHOLOGICAL CHANGES - Bakhriddinova Nargiza Jaloliddin qizi (Open Academia, 2024)
The article shows that the relationship between parents and teenagers in the family depends on the family culture, that is, the family has a high and responsible task of raising young people to be perfect people, parents are extremely responsible for the education of children, the role model established in the family An opinion was expressed about the influence of order and positive customs on children's education
Keywords: Psychology; child; education; family